MAKNA RUANG GENERASI MILENIAL BERDASARKAN PENDEKATAN PLACE ATTACHMENT PADA KEDAI KOPI DI JAKARTA - Sulistyawati, Dwi
The millennial generation is a generation that has grown since childhood in a community environment where the majority use gadgets. Currently, they are a productive generation that has a fairly high dependence on gadgets, because their activities are facilitated by the very rapid development of Information Technology (IT). Their real space preferences are influenced by this, where space not only serves as a facility, but also as a place that gives them a special meaning. For millennials, space is a tangible and imaginary facility, reflecting their need for comfort, connectivity, and meaningful experiences. Coffee shops are the most popular facilities for millennials, where they often do activities alone or together. The author research how the millennial generation interprets public space, with a case study on coffee shops as a place of their activities. In coffee shops, millennials not only enjoy coffee, but tend to spend long hours enjoying the atmosphere, doing something on their own, or hanging out with relatives. This research method uses the Mix-Method category of exploratory properties of the type of Explanatory Sequential Mixed Methods Design. Exploration of sequential mixed method design with three-stage design. This design aims to explore research problems related to the preferences of the millennial generation in interpreting places in public spaces. Exploratory research refers to the initial research that lays the foundation for the next stage of research. Data processing in phase 1 research using the CFA (Confirmatory Factor Analysis) method was obtained through a closed questionnaire and disseminated through online media. The questionnaire uses 7 likert scales that revolve around the preferences of the millennial generation towards public space through the framework of the Place Attachment theory through 3 references (Topophilia, Place Dependence and Place Identity). The theory produced 56 questions consisting of 3 parts, namely, (1) 17 questions related to Topophilia, (2) 21 questions related to place dependence, and (3) 11 questions related to place identity. There are 6 factors that are formed with 20 dimensions through confirmatory factor analysis. Topophilia has 2 factors that are formed from 7 dimensions, namely (1) Natural zoning with 4 dimensions (natural materials, natural styles, natural lighting and iv natural air circulation) and (2) Zoning of odors with 3 dimensions, (there are smoking areas, non-smoking areas, and odorscapes). Place dependence has 2 factors formed from 6 dimensions, namely (1) Personal zoning with 3 dimensions (quiet space, self-work area in public space, and space cleanliness) and (2) Feature zoning with 3 dimensions (There are power plugs, free Wi-Fi, activating gadgets without obstacles). Place Identity has 2 factors that are formed from 6 dimensions, namely (1) Narcissistic zoning with 3 dimensions (many spots for selfies, instagramable, there are reviews of places in online media) and (2) Zoning with 3 dimensions (good food/drinks, modern style, and a space with a simple atmosphere). The dimensions that are formed are interpreted into the meaning of space for the millennial generation as the meaning of perception, the meaning of association and the meaning of Connotation. The data obtained in the second phase of research is the validation of the findings of the first stage through direct observation in the field through hidden recordings to see the mapping of the activities and behaviors of the millennial generation in coffee shops through the criteria from the previous findings of the first stage. Information obtained through interviews with the millennial generation as users when coffee shops are open on weekdays and weekends. Closed observation is focused on the behavior of the millennial generation's activities as users of space and facilities and infrastructure in the coffee shop. The data obtained were then described and associated with the theory of Place Attachment as a positive emotional association with coffee shops that can be indicated by the attachment of space for the millennial generation with a feeling of pleasure, a feeling of belonging, a feeling of satisfaction, a feeling of dependence and a feeling of belonging or making the place part of their identity. In the third stage of the research, verification was carried out on the results of the research in the previous two stages which referred to the main purpose of the research on the meaning of public space for the millennial generation. This is characterized by attachment to space through observation of behavioral activity preferences and interviews with respondents who are in coffee shops, which are then described in the form of descriptions. The meaning of space for the millennial generation can be associated with "Place is more than as a friend" and space as the meaning of the CCP symbol "Connectivity", "Comfortability" and "Productivity" is shown through its attachment to a place in public spaces, especially coffee shops.